The atlas of untold stories [large type] - Brunsvold, Sara, 1979- (Center Point Large Print, 2025)
"Irrepressible dreamer Chloe Vance needs to tell her pragmatic mom, Edie, that she has accepted a low-paying, two-year art instructor role at a Christian international school in Prague. And her older sister, Lauren--'the responsible one'--is doing all she can to keep the family from finding out she has been fired for a stupid mistake, plus figure out her next career move. Meanwhile, Edie, estranged from her own sister following their mother's recent death, is frankly in no mood for anything else to change. The one thing they can all agree on? Life in books sure is easier to figure out than life in the real world. As the three women embark on a nine-day road trip to visit significant literary sites throughout America's heartland, they hope to find inspiration through the works and lives of literary greats. And as they experience firsthand the adventure and wonder of the classics, they'll have to come to terms with their own needs and desires, as well as those of the most important women in their lives--each other."--